ANALISIS KORELASI INDEKS PLASTISITAS TERHADAP PARAMETER KUAT GESER TANAH PADA TANAH LEMPUNG MANYAR GRESIK - Hamzah, Yayu Sriwahyuni; Judiono, Judiono; Mauludin, Ahmad Nur Radit; Wahyono, Cyril Omar (Fakultas Teknik Universitas Palangka Raya, 2026)
Clay soil is a type of soil characterized by high plasticity and strong sensitivity to changes in water content, which can significantly affect construction stability. Shear strength parameters, namely cohesion (c) and internal friction angle (φ), are essential factors in geotechnical analysis; however, their determination generally requires considerable time and cost. Therefore, an alternative approach is needed by utilizing the Plasticity Index (PI) as a predictive parameter for soil shear strength. This study aims to analyze the relationship between the plasticity index and the shear strength parameters of clay soil in Manyar District, Gresik Regency.The research employed a quantitative approach based on laboratory testing, including Atterberg limits tests to determine the plasticity index and direct shear tests to obtain cohesion and internal friction angle values. The analysis was conducted at several soil depths using descriptive and empirical regression approaches.The results indicate that the plasticity index ranges from 41.97% to 47.84%, with cohesion values between 0.25–0.39 kg/cm² and internal friction angles ranging from 7° to 15°. The analysis shows that an increase in the plasticity index tends to be followed by an increase in cohesion and a decrease in the internal friction angle. These conditions indicate that the soil at the study site is predominantly cohesive with a relatively high deformation potential. The findings of this study are expected to serve as a preliminary approach for estimating shear strength parameters in similar clay soil conditions.